Cyber security Crimes, weaknesses, and modern practical applications in solution - Yasser Elmalik Ahmed Seleman, (International Journal of Computers and Informatics, 2025)
The research deals with a group of problems and breakthroughs in the previous period and the largest attacks in history that caused failures in technical systems around the world. The research discussed cyber-attacks and disruptions and how to deal with them, better understand the difference, and enhance cyber security. Through the research, many examples of malfunctions, hacks, and cyber-attacks on modern global systems are discussed. The research aims to identify the basic causes, weaknesses, and methods that contribute to finding solutions security and the challenges of espionage and electronic penetration of countries through cyberspace ، it aims to clarify the various cyber challenges and risks that threaten the security of countries.
Keywords: Cyber Security; Electronic hacking; Cyber Space